Choledochal Cyst: Case Variations and Management - Girsang, Andrew Deardo Purba; Fattahillah T, Rizqy Agung; Nazilinly, Fitri; Kamilah, Nilam Nurmilatun; Pramudya, I Nengah Andra Putra; Mario, Andina Nabilah; Faqih, Fauzan; Zuhan, Arif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Choledochal Cyst (CC) is a congenital anomaly characterized by the dilation of intrahepatic and/or extrahepatic bile ducts. This condition can occur at any age but is more common in infants and children, accounting for 80% of cases. This study aims to evaluate the clinical characteristics, diagnostic approaches, and optimal management options for choledochal cysts, accompanied by case variations. The method used in this study is a literature review, gathering relevant literature from various references focused on the topic of choledochal cysts. Literature searches were conducted using library search websites, including PubMed, ScienceDirect, Cochrane Library, Google Scholar, and ProQuest, with the search keyword